Analisis Arsitektur Enterprise Sistem Pemerintahan Berbasis Elektronik Menggunakan Kerangka Kerja TOGAF ADM (Studi Kasus: Disparbud Kabupaten Bandung Barat) - Dicky Yudha Handika; Rahmat Mulyana; Nia Ambarsari (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2019)
In supporting government programs, namely the Electronic Government (e-Government), the Department of Tourism and Culture of West Bandung Regency which specifically handles Public Employment and Cultural Development is needs to harmonize business services and information solutions in relation to the internal aspects of the community development and development potential for the West Bandung Regency community. Enterprise Architecture (EA) is the answer to the IT blueprint documentation of development plan. The design of EA in this study uses the TOGAF ADM framework to meet system development needs through Phase C: Information System Architecture (Data Architecture & Application Architecture). Document analysis, interviews and observations was carried out in supporting the research of the organization's information needs during the development of EA. The results obtained in the form of data and application integration solutions through Government Service Bus (GSB) technology.